Overcoming prejudice, seeking support: Transnational social media communication of female Vietnamese students in South Korea and Singapore. Issue 2 (1st October 2018) - An, Soontae; Lim, Sun Sun; Lee, Hannah; Pham, Becky
This study examined the role of social media in the daily lives of migrant students. The focus of this study was students' use of social media and the benefits that they derived from it, particularly for communication with friends and family back in their home country. A total of 45 female Vietnamese students participated in a week-long social media-deprivation exercise in which they abstained from using social media to connect with friends and family in Vietnam and/or focus group discussions on their daily communication practices. A cross-cultural comparison was conducted to evaluate the differences between twenty Vietnamese students living in South Korea and 25 Vietnamese students living in Singapore. The findings indicate key differences in the sociocultural environment that influence their social media communication. Vietnamese students in South Korea drew closer to their co-national friends due to stronger perceptions of discrimination than their counterparts in Singapore, who integrated more easily into the multi-cultural environment. The findings suggest that international students should optimize their social media use to build diverse and encompassing social networks that are mutually reinforcing rather than mutually exclusive to facilitate adaptation.